2020
DOI: 10.1155/2020/2780378
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Work-Related Risks among Veterinary Clinical Students in South West Nigeria

Abstract: Veterinary practices or activities expose professionals, including students, to hazards associated with animal contact. To describe workplace health and safety status and risk factors associated with hazards among veterinary clinical students in South West Nigeria, a cross-sectional survey was conducted using a semistructured questionnaire. Data on demographics, health and safety (HS) status, work-related hazards, healthcare facilities, and immunisation history were obtained. Of 167 students recruited, 100 (60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
8
9
0
Order By: Relevance
“…The study revealed a higher number of male respondents than females. This is similar to previous studies which showed a reflection of male dominance in the veterinary profession in Nigeria (Odetokun et al, 2019;Adebowale et al, 2020;Adenubi et al, 2020b). Female veterinary students who participated in this study (40.5%), when compared with a similar and recent study conducted among veterinary professionals with 27.2% female respondents seems higher (Adenubi et al, 2020b).…”
Section: Discussionsupporting
confidence: 92%
“…The study revealed a higher number of male respondents than females. This is similar to previous studies which showed a reflection of male dominance in the veterinary profession in Nigeria (Odetokun et al, 2019;Adebowale et al, 2020;Adenubi et al, 2020b). Female veterinary students who participated in this study (40.5%), when compared with a similar and recent study conducted among veterinary professionals with 27.2% female respondents seems higher (Adenubi et al, 2020b).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, veterinarians are exposed to diverse forms of hazards in their workplace. Significant physical hazards, particularly the needlestick injuries (NSI) (75.0%; 95% CI: 68.0–82.0%, p< 0.001) and cumulative traumatic disorder (CTD) (25%; 95% CI: 23.0–27.0%, p< 0.001) among veterinarians has been a source of worries for professionals due to their high prevalence [4,5,7,9,38]. NSI remains a major hazard and issue in the veterinary profession especially with regards to recapping of needles and consequent accidental needle prick [9].…”
Section: Discussionmentioning
confidence: 99%
“…NSI remains a major hazard and issue in the veterinary profession especially with regards to recapping of needles and consequent accidental needle prick [9]. Besides, frequent contact with and handling of large animals such as pigs, goats and sheep increased the risk of NSI in veterinary students [38]. The lack of in-depth understanding of animal behaviour (ethology), improper handling and disposal of needles, and poor or inadequate restraint techniques applied to these large animals predispose to increased risk of NSIs [38].…”
Section: Brucella Speciesmentioning
confidence: 99%
See 2 more Smart Citations